Melatonin protects against Aβ‐induced neurotoxicity in primary neurons via miR‐132/PTEN/AKT/FOXO3a pathway. (11th January 2018) - Zhao, Yue; Zhao, Ranran; Wu, Jintao; Wang, Qian; Pang, Kunkun; Shi, Qingqing; Gao, Qing; Hu, Yanlai; Dong, Xiaoguang; Zhang, Jing; Sun, Jinhao
Abstract: Alzheimer's disease (AD) is a kind of neurodegenerative disorder associated with age. Investigations suggest that amyliod‐β (Aβ) is implicated in the pathogenesis of AD. The accumulation of Aβ in the brain causes oxidative stress and synaptic toxicity, leads to synaptic dysfunction and neuronal death. Previous investigations suggest that melatonin an endogenous hormone can counteract Aβ‐induced neurotoxicity. However, the molecular mechanisms of Aβ‐induced toxicity and melatonin treatment remain elusive. Studies indicate that microRNA‐132 is crucial for neuronal survival and plays a key role in the pathological process of AD. Moreover, PTEN and FOXO3a two key targets of miR‐132 are upregulated in the AD brain. Here, we exposed the primary cultured cortical neurons with Aβ25‐35 and treated with melatonin. Our investigations demonstrated that Aβ25‐35 exposure significantly decreased the expression of miR‐132 and elevated the expression of PTEN and FOXO3a. Whereas, melatonin treatment could rescue the expression of miR‐132 and downregulate the level of PTEN and FOXO3a. Moreover, melatonin blocked the nuclear translocation of FOXO3a and thereby suppressed its pro‐apoptotic pathways. In addition, our investigations suggested that the over‐expression of miR‐132 could block Aβ‐induced neurotoxicity. We also found that VO‐OHpic (PTEN inhibitor) could counteract Aβ‐induced neuronal damage, and LY294002 (AKT inhibitor) suppressed the protective effect of melatonin. Together, these results indicate that melatonin exerts its neuroprotective effect in Aβ‐induced neurotoxicity via miR‐132/PTEN/AKT/FOXO3a pathway. © 2018 BioFactors, 44(6):609–618, 2018